CORRECTION OF MALFUNTION FROM THE SIDE OF PAROTID GLANDS IN PATIENTS WITH NEUROGENIC SIALOADENITIS AND HER RESULTS - Gavrilyev, V.M.; Ribalov, O.V. (World of Medicine and Biology, 2012)
For the correction of malfunction from the side of parotid glands, a patient, taking into account of degree of weight of neurogenic sialadenosis, was prescribed gleam increase of channels of the interested glands, their massage, installation at the channel of ectericidi, proteolytics enzymes (Trypsinum), electrophoresis of 5 % solution of ascorbic acid on the area of the staggered glands, professional hygiene of cavity by stomatologist-therapeutist, "Sedasen forte", "No-Spa", retinol acetate, multivitamin complex "Alphavit". Treatment andpreventive measures providing to patients with neurogenic sialadenosis promoted to liquidation in near terms in most patients of inflammatory process in the staggered glands (from data of cytological research of secret), improvement of the general somatic state of patients.
Keywords: neurogenic; sialadenosis; correction; treatment